Mie lidar and radiosonde observations at Gadanki (13.5°N, 79.2°E) during sudden stratospheric warming of 2009 - Sridharan, S.; Raghunath, K.; Sathishkumar, S.; Nath, D. (My University, 2011)
During a major sudden stratospheric warming event (21–27 January 2009), Mie-lidar observations at Gadanki (13.5°N, 79.2°E) show persistent occurrence of cirrus clouds. Outgoing long-wave radiation averaged for 70°E–90°E, decreases to a low value (170 W/m2) on 27 January 2009 over equator indicating deep convection. The zonal mean ERA-Interim data reveal large northward and upward circulation over equatorial upper troposphere. The latitude–longitude map of ERA-Interim zonal mean potential vorticity (PV) indicates two tongues of high PV emanating from polar latitudes and extending further down to equator. Radiosonde observations at Gadanki show the presence of ∼40% relative humidity at 11–13 km and lower tropopause temperature. It is inferred that the tropical circulation change due to PV intrusion leads to deep convection, which along with high humidity and low tropopause temperature leading to the formation of persistent cirrus clouds, the occurrence frequency of which is normally less during winter season over Gadanki.
Keywords: Stratospheric warming; Meridional circulation; Tropical convection; Cirrus clouds; Sudden stratospheric warming